Thidiazuron and trans-zeatin riboside promote development of shoots and nodes in in vitro propagation of hops (Humulus lupulus L. var. lupulus) - Staats, Elise R.; Jenderek, Maria M. (Frontiers in Plant Science, 2026)
Hops (Humulus lupulus L. var. lupulus) are dioecious, climbing plants considered as a horticultural and industrial crop. They are propagated vegetatively by root cuttings and, to a lesser extent, by tissue cultures. Various plant growth regulators were applied in hops’ tissue culture propagation, such as benzyladenine, kinetin, indole-3-acetic acid, thidiazuron, zeatin, and gibberellic acid, and some in combination with glucose. In vitro propagation of three randomly selected genotypes (PI 546055, PI 558687, and PI 617389) from the US Department of Agriculture (USDA) Agricultural Research Service (ARS) hop germplasm collection was carried out to establish a procedure for developing a large quantity of shoots, nodes, and long main shoots using 15 treatments of plant growth regulators and glucose without plant growth regulators. The micropropagation was carried out in three propagation cycles lasting 4 weeks each. The largest number of shoots and nodes resulted from treatments with thidiazuron (15.9 ± 1.34 shoots; 40.6 ± 3.6 nodes). Literature has reported the successful use of this plant growth regulator in selected hop cultivars, but thidiazuron caused hyperhydricity in PI 546055. The occurrence of hyperhydricity in this accession seems to be genotype-dependent. Hence, its use in hop micropropagation should be controlled. The disorder was not observed in the other treatments. In the 3.0 mg L−1 of trans-zeatin riboside treatment, the shoot number (8.4 ± 1.34) and node number (24.9 ± 3.6) were not much different from those of the thidiazuron treatments, and the length of the main shoots (9.3 ± 0.92 cm) was not significantly different from that of the other treatments, except for the thidiazuron treatments. The 3.0 mg L−1 of trans-zeatin riboside was the top treatment for the micropropagation of the three hop accessions. This treatment will be used for a variety of accessions from the USDA hop germplasm collection. It may also be useful when large quantities of plantlets are needed for other purposes and when the responsiveness to thidiazuron (TDZ) is unknown.